Clinical outcome, role of BRAFV600E, and molecular pathways in papillary thyroid microcarcinoma: is it an indolent cancer or an early stage of papillary thyroid cancer? - Carmelo eNucera; Alfredo ePontecorvi (Frontiers in Endocrinology, 2012)
Most human thyroid cancers are differentiated papillary carcinomas (PTC). Papillary thyroid microcarcinomas (PTMC) are tumors that measure 1 cm or less. This class of small tumors, recognized fairly recently, has proven to be a very common clinical entity in endocrine diseases. PTMC may be present in 30-40% of human autopsies and is often identified incidentally in a thyroid removed for benign clinical nodules. Although PTMC usually has an excellent long-term prognosis, it can metastasize to neck lymph nodes; however deaths related to this type of thyroid tumor are very rare. Few data exist on molecular pathways that play a role in PTMC development; however, two molecules have been shown to be associated with aggressive PTMC. S100A4 (calcium-binding protein), which plays a role in angiogenesis, extracellular matrix remodeling, and tumor microenvironment, is over-expressed in metastatic PTMC. In addition, the BRAFV600E mutation, the most common genetic alteration in PTC, is present in many PTMC with extra thyroidal extension and lymph node metastasis. Importantly, recently developed selective (e.g. PLX4720, PLX4032 (Vemurafenib, also called RG7204)) or non-selective (e.g. Sorafenib) inhibitors of BRAFV600E may be an effective treatment for patients with BRAFV600E-expressing PTMCs with aggressive clinical-pathologic features. Here, we summarize the clinical outcome, cancer genetics, and molecular mechanisms of PTMC.